Inclusion of solar energy in iraq gas-turbine power plants as a method of solving the country's energy system shortage - A. Z. Abass; D. A. Pavlyuchenko; A. M. Balabanov; V. M. Less (Известия высших учебных заведений: Проблемы энергетики, 2020)
At high ambient temperatures, the performance of gas turbine power plants drops significantly. Technical solutions of compensation for losses associated with the constant injection of water into the air intake of a gas turbine. This approach is not acceptable in regions with limited fresh water reserves. Radical solutions are required to reduce the cost of generated energy. Integrated Combined Solar Cycle (ISCCS) technology has proven itself on many projects. The addition of a combined cycle gas cycle with solar energy can significantly increase the overall efficiency of the power plant. Despite the increase in costs during the construction of its solar part, the total cost of operating solar collectors is several times less than a turbine installation. Given the global trend to fight carbon emissions, switching to a hybrid scheme is economically attractive. Trading in carbon credits for CO2 emissions will significantly reduce the payback period for the construction of gas turbine modernization under the ISCCS scheme. This paper presents an option to modernize a gas turbine power plant in the city of Basra (Iraq), using the advantages of solar radiation and recycling of combustion products from gas turbines. It is proposed to equip the existing 200 MW gas turbine plant with two steam turbine units with a capacity of 75 and 65 MW, working in conjunction with solar collectors producing low pressure water vapor. Due to modernization, the efficiency of the power plant should increase from 38% to 55%. The revision of the schematic and technical solutions of Iraq power plants will allow producing sufficient energy for the region.